The Reading Strategies and Challenges Used to Develop Primary Students’ Reading Skills - Putu Paradila Sita Anugrah; Ni Putu Era Marsakawati; Suarcaya Putu (Universitas Islam Negeri Palopo, 2025)
The current study aims to find the reading strategies and challenges faced by eighth-grade students at SMPN 2 Tampaksiring. The strategies were obtained based on three reading categories: cognitive, metacognitive, and socio-affective. There were 30 eighth-grade students involved in this study who were selected by using cluster sampling. Meanwhile, only 3 students were selected by using purposive sampling as the informants for the interview section. The data were collected through observation and semi-structured interviews. The research instruments were an observation sheet and an interview guide. The data were analyzed by using the Qualitative Data Analysis method, which consisted of four stages: data collection, data reduction, data display, and conclusion drawing. Data triangulation and method triangulation were conducted to ensure data trustworthiness of the current study. The results showed that 1) three kinds of learning strategies are employed by students at SMPN 2 Tampaksiring to enhance English reading skills, covering cognitive strategies, metacognitive strategies, and socio-affective strategies; and 2) five challenges are encountered in using reading strategies, covering limited vocabulary, low comprehension, strategy application, lack of motivation, and anxiety. The present study relates to education, where the strategies are beneficial for engaging students in reading activities. It highlights the importance of integrating explicit strategy instruction into the English curriculum.